The Burden of Asthma in Children Aged 0-14 Years in Asia: A Systematic Analysis for the Global Burden of Disease Study 2019 - Elham Goodarzi; Kobra Rashidi; Zahra Zare; Vectoria Momenabadi; Zaher Khazaei (Galenos Yayinevi, 2022)
Aim:Asthma is the most common chronic disease in children and it imposes a huge burden on the health systems of countries. The aim of the present study was to investigate the burden of asthma disease in children in Asia during the period of 1990-2019.Materials and Methods:All data sources from the Global Burden of Disease study (2019) were used to estimate the breast cancer prevalence, mortality, disability-adjusted life years and asthma rates in children aged 0-14 years in Asia from 1990 to 2019. We estimated all-cause and cause-specific mortality, years of life lost (YLLs), years lived with disability (YLDs), disability-adjusted life years and attributable risks.Results:There is a positive and significant correlation between the human development index (HDI) and disease incidence in both sexes (r=0.417, p<0.05), and this correlation is positive and significant in both females (r=0.401, p<0.05) and males (r=0.420, p<0.05). There is also a significant negative correlation between HDI and disease mortality in both sexes (r=-0.475, p<0.05) and this negative correlation is significant in both females (r=-0.459, p<0.05) and males (r=-0.483, p<0.05). The study of YLDs showed that there is a significant negative correlation between HDI and YLL in both sexes (r=-0.474, p<0.05), and in women (r=-0.456) and men (r=-0.483, p<0.05).Conclusion:Given that YLL is higher in countries with low HDI, greater attention must be paid to reduce the incidence of and premature deaths attributable to asthma in these countries.